Representation of Violence Against Women in the Novel Rumah untuk Alie by Leen Liu (An Existentialist Study of Simone de Beauvoir) - Arina, Ukhtul Iffah Daat; Vardani, Eka Nova Ali; Citraningrum, Dina Merdeka (Journal of Language and Literature Studies, 2025)
This study examines the representation of violence against women in Leen Liu’s novel Rumah untuk Alie, which reflects the persistence of patriarchal domination and gender inequality in Indonesian society. The research aims to describe the forms of violence physical, emotional, and sexual, experienced by the female character and to analyze how these acts of violence position women as “the Other” through Simone de Beauvoir’s existentialist feminist perspective. The study employs a descriptive qualitative method with textual analysis and data triangulation to ensure the validity of the findings. The results reveal that the female protagonist, Alie, experiences various forms of violence both in domestic and public spheres, such as physical abuse by her father, emotional neglect by her family, and sexual harassment in her social environment. These acts of violence symbolize systemic patriarchal control that confines women to a state of immanence, limiting their autonomy and subjectivity. Through Beauvoir’s theoretical lens, the novel exposes the philosophical significance of such oppression, how women’s bodies and existence are reduced by male dominance while still yearning for transcendence and self-liberation. This study contributes to a deeper understanding of women’s existential struggle and emphasizes the importance of gender awareness in literature as a means of promoting equality. Moreover, the findings hold broader societal implications by highlighting the structural nature of gender-based violence and underscoring the practical significance of these results in promoting gender equality and fostering social awareness to combat systemic oppression.